Effect of chemical modifications and electron beam irradiation on properties of corn cob filled chitosan biocomposite films - Chan, Ming Yeng (School of Materials Engineering, 2015)
In present work, the CS/CC biocomposite films were prepared via solvent casting method. The tensile properties such as tensile strength, modulus of elasticity, and elongation at break were investigated. The scanning electron microscopy (SEM) was carried out to investigate the filler-matrix interaction and filler dispersion. Furthermore, the thermal properties of CS/CC biocomposite films were also studied by using thermogravimetry analysis (TGA). Fourier transform infrared (FTIR) spectroscopy was used to investigate the functional groups of CS/CC biocomposite films. The biodegradation test such as enzymatic and soil degradation methods were used to measure the biodegradability of CS/CC biocomposite films. The gel fraction method can be used to determine the degree of crosslinking of CS/CC biocomposite films. The electron beam irradiation was carried out to study the effect of radiation-induced crosslinking on properties the CS/CC biocomposite films.